Analysis of the Effect of Blade Washing Compressor on Compressor Efficiency and Thermal Efficiency of Gas Turbine at PLTG XXX - Susanto, Edy; Sinambela, Hotdian; Tri Khairullah, Rafi (DINAMIS, 2025)
The most important parts of a gas power system are the compressor and gas turbine. Compressor performance will naturally decrease due to high ambient temperatures and dirt in the incoming air and make the compressor inefficient. To restore compressor efficiency, it is recommended to clean the compressor using the compressor blade washing method. The purpose of this study was to determine the compressor blade washing procedure used in the PLTG system and determine the parameters tested and analyses their effect on the thermal efficiency of the PLTG. This study was conducted on a PLTG unit operating at a load of 120 MW or 50% of the installed capacity, with research stages including data collection, calculation of the gas turbine heat rate, calculation of the thermal efficiency of the PLTG cycle and calculation of compressor efficiency. From the implementation of the compressor blade washing carried out, there was an increase in compressor efficiency of 2.62% and after the compressor blade washing caused a decrease in the heat rate of 853 kJ / kWh, so that there was an increase in the thermal efficiency of the PLTG of 1.74%.